Gambaran Terapi Kombinasi Ranitidin Dengan Sukralfat Dan Ranitidin Dengan Antasida Dalam Pengobatan Gastritis di SMF Penyakit Dalam Rumah Sakit Umum Daerah (RSUD) Ahmad Mochtar Bukittinggi - Isna Wardaniati; Almahdy Almahdy; Azwir Dahlan (STIFARM Padang, 2016)
Gastritis is the most common disease found in the community. Everyday frequently we can find patients with upper gastrointestinal problems visit health installation service to cure their disease, such as pain problems or burning sensation in epigastrum area, sometimes followed by regurgitation, stomach heartburn, bloating sensation and early satiety. In gastritis medications, a single therapy is usually preferred, but there are also some using the combination of two drugs. The common drugs being used is based on gastritis conditions level. In this research, the observed drug combination were ranitidine with sucralfat and ranitidine with antacids. The description of drugs used was being judged based on clinical symptoms and endoscopy examination. The confirmed gastritis patients were divided into two groups. Afterwards, the patient were given the therapy( ranititidine and sucralfat) and (ranitidine and antacids) for two weeks. After 4 months since the therapy was being given, the evaluations of patients conditions was done, including the pain in gastrointestinal tract, nausea, regurgitate, smarting before and after meal, burning sensation in the stomach, early satiety and bloating. From evaluations examinations in to the two groups, we founds the results that in groups I the complaint was dissolved about 100 % and in groups II was about 80 %.